2021
DOI: 10.3390/cancers13061308
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio Predicts Development of Immune-Related Adverse Events and Outcomes from Immune Checkpoint Blockade: A Case-Control Study

Abstract: The utility of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) utility in predicting immune-related adverse events (irAEs) and survival have not been well studied in the context of treatment with immune checkpoint inhibitors (ICIs). We performed a case-control study of cancer patients who received at least one dose of ICI in a tertiary hospital. We examined NLR and PLR in irAE cases and controls. Logistic and Cox regression models were used to identify independent risk factors for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 34 publications
(47 reference statements)
3
44
2
Order By: Relevance
“…Several studies have reported the relationship between NLR and immune-related adverse events in patients with malignancies treated with immune checkpoint inhibitors [36][37][38]. However, the relationship between adverse events and NLR in patients with HCC treated with Atez/Bev has not been sufficiently investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the relationship between NLR and immune-related adverse events in patients with malignancies treated with immune checkpoint inhibitors [36][37][38]. However, the relationship between adverse events and NLR in patients with HCC treated with Atez/Bev has not been sufficiently investigated.…”
Section: Discussionmentioning
confidence: 99%
“…An isolated rise in neutrophil count, and, consequently, an elevated NLR, can be observed in several conditions: bacterial or fungal infection [ 4 , 5 , 6 ], acute stroke [ 7 ], myocardial infarction [ 8 ], atherosclerosis [ 9 ], severe trauma [ 10 ], cancer [ 11 ], post-surgery complications [ 12 ] and any condition characterized by tissue damage that activates SIRS. This is because the early hyperdynamic phase of infection is characterized by a proinflammatory state, mediated by neutrophils and other inflammatory cells [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…atezolizumab, durvalumab and avelumab) are now standard and effective anticancer agents serving as the backbone of cancer therapy for a wide range of cancer types (1,(4)(5)(6). However, the same enhancement of the immune response can give rise to undesirable, off-target and inflammatory immune-related adverse events (irAEs) (2,7). A range of irAEs have been described to occur in almost every organ system, ranging from mild to high grade irAEs that can be fatal (8).…”
Section: Introductionmentioning
confidence: 99%